Ontological Metaphors in Selected Songs of MLTR’s Greatest Hits Album: A Cognitive Semantic Study - Nehemia Anugrah Parasian (Universitas Sebelas Maret, 2026)
This study aimed to classify ontological metaphors and interpret the conceptual mappings found in four selected songs by Michael Learns to Rock (MLTR) from their Greatest Hits album. Using the theoretical framework of Conceptual Metaphor Theory (CMT) by Lakoff and Johnson, this qualitative research analyzed the lyrics to identify metaphorical expressions that conceptualize abstract experiences through concrete entities. The findings revealed that ontological metaphors are manifested in various forms, including personification (e.g., love is treated as a human entity), substance metaphors (e.g., feelings treated as tangible objects), and container metaphors (e.g., the heart as a space to hold emotions). The conceptual mapping identified source domains such as human, object, and space, which are mapped onto target domains such as emotion, love, loss, and time. These metaphors help listeners conceptualize intangible experiences more concretely and emotionally. The study concludes that ontological metaphors play a crucial role in shaping emotional resonance and poetic imagery in song lyrics.